Time-Cost Estimation Probabilistic Model Using MCS in Quantitative Risk Analysis in BOT Renewable Energy Projects - Yaghoubi, Dariush; Dorodiyan, Mahmoud; Adibi, Mohammad Amin (International Journal of Industrial Engineering and Management, 2022)
The purpose of this study is to investigate the impacts of risks in the construction and operation period of BOT waste-to-energy projects, and the estimation of the final costs. In this study, the cost and impact of identified risks on the activities of the construction and operation phase are estimated, then the time and cost of a waste-to-energy project are calculated. The results of this study indicate that simultaneous and continuous consideration of risk effects such as inflation, sanctions, and maintenance in projects leads to much different time and cost than the forecasted fixed costs; that is, in the case of an error by the private sector in the determination of the operation period, the project might be faced with delays and ultimately failure. Article history: Received (March 23, 2022); Revised (November 17, 2022); Accepted (November 22, 2022); Published online (November 28, 2022)